The classrooms as learning communities - Maphalala, Mnecidisi Christian (The IIE, 2017)
Classrooms are sites in which learning takes place through interactions with others and learners are given opportunities to construct knowledge, and to acquire skills, values and attitudes. Classrooms in which learners and teachers learn together and contribute to knowledge construction are called ‘learning communities’. Learning communities as an area of study have been under researched despite the fact that there is a body of research that indicates that learning is a collaborative activity rather than an individual exercise, which brings with it significant benefits. This paper argues that effective learning takes place in a collaborative learning environment in which both teachers and learners work together to construct knowledge, and proposes ways in which classrooms as learning communities can function.
Keywords: Learning community; Community of practice; Classrooms; Knowledge construction; Collaborative learning